Generative AI Text Classification using Ensemble LLM Approaches - Abburi, Harika; Suesserman, Michael; Pudota, Nirmala; Veeramani, Balaji; Bowen, Edward; Bhattacharya, Sanmitra (arXiv, 2023)
Large Language Models (LLMs) have shown impressive performance across a variety of Artificial Intelligence (AI) and natural language processing tasks, such as content creation, report generation, etc. However, unregulated malign application of these models can create undesirable consequences such as generation of fake news, plagiarism, etc. As a result, accurate detection of AI-generated language can be crucial in responsible usage of LLMs. In this work, we explore 1) whether a certain body of text is AI generated or written by human, and 2) attribution of a specific language model in generating a body of text. Texts in both English and Spanish are considered. The datasets used in this study are provided as part of the Automated Text Identification (AuTexTification) shared task. For each of the research objectives stated above, we propose an ensemble neural model that generates probabilities from different pre-trained LLMs which are used as features to a Traditional Machine Learning (TML) classifier following it. For the first task of distinguishing between AI and human generated text, our model ranked in fifth and thirteenth place (with macro $F1$ scores of 0.733 and 0.649) for English and Spanish texts, respectively. For the second task on model attribution, our model ranked in first place with macro $F1$ scores of 0.625 and 0.653 for English and Spanish texts, respectively.
arXiv:2309.07755 [cs] <标题>: 使用集成大语言模型方法的生成式人工智能文本分类 Read_Status: New Read_Status_Date: 2026-01-26T11:32:28.375Z
Keywords: Computer Science - Artificial Intelligence; Computer Science - Computation and Language